Non-Suicidal Self-Injury in College Students: Differences Between the Subject Group and Comparison Group - Kim, Hye-seung; Seo, Yong-won; Lee, Youngil; Lee, Chang Min; Kim, Do Hyun; Kim, Minsun; Lim, Myung Ho (Psychiatry international (Basel), 2025)
In recent years, self-injury attempts have accounted for 46.2% of emergency room visits by teenagers and young adults. This study aimed to explore the prevalence of non-suicidal self-injury (NSSI) among Korean college students, compare the mean number of NSSI risk factors between those with a history of NSSI and a control group with no history of thoughts or experiences of self-injury, and identify which factors have a greater influence on NSSI. The participants consisted of 403 Korean college students aged 18–29 who were divided into a subject group with a history of NSSI (n = 198) and a comparison group (n = 205) with no history of NSSI. The Functional Assessment of Self-Mutilation (FASM), Childhood Trauma Questionnaire (CTQ-SF), Social Experience Questionnaire (SEQ), Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder 7-item scale (GAD-7), Difficulties in Emotion Regulation Scale—16 item version (DERS-16), Experiences in Close Relationship Questionnaire-Revised (ECR-R), Rosenberg Self-Esteem Scale (RSES), Parents as Social Context Questionnaire-Kids (PSCQ-KA), and Barratt Impulsiveness Scale-11-Revised (BIS-11). The collected data were analyzed using SPSS 25.0. Before a regression analysis, a MANOVA was performed to examine the mean difference between groups of each dependent variable, and a multiple regression analysis was performed to confirm the influence. The mean difference in all risk factors in the subject group compared with the comparison group was found to be statistically significant, with an effect size of 0.8 or greater. As a result of examining the relative influence of each variable on NSSI, emotional dysregulation (t = 2.481, p = 0.014), anxiety (t = −2.109, p = 0.036), and adult attachment (t = 2.004, p = 0.046) were found to significantly influence NSSI (p = 0.05). These findings will serve as fundamental data for screening clients at risk of self-injury in counseling and treatment settings, in addition to providing preventive and therapeutic interventions.